Relation between serum vitamin B12 level and duration of treatment with carbamazepine in epilepsy patients - Islam, Mohammad Tariqul; Sobhan, Khair M.; Shawly, Mahjabin Rahman; Saleheen, Shafiqur; Emran, Mohammad Masum; Hannan, M. A. (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Vitamin B12 levels in the serum of 58 epileptic patients receiving only carbamazepine for at least 6 months were measured. Same number of epilepsy patients with no history of taking antiepileptic medicine were taken as control. The mean level of vitamin B12 in carbamazepine-treated epileptic patients was 265.5 pg/mL whereas it was 478.3 pg/mL in control. Increased duration of treatment of carbamazepine in epilepsy caused significantly decreased level of serum vitamin B12 (Pearson correlation coefficient, r = -0.9, p<0.0001). In conclusion, serum vitamin B12 level significantly decreased in relation to duration of carbamazepine treatment in epileptic patients.